2016
DOI: 10.1787/5jlpq7v3j237-en
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Decentralisation and Regional Disparities

Abstract: JT03401144Complete document available on OLIS in its original format This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. ECO/WKP(2016) The statistical data for Israel are supplied by and under the responsibility of the relevant Israeli authorities. The use of such data by the OECD is without prejudice to the status of the Golan Heights, Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…The number of causes of regional divergence identified by these methods is quite large. Thus, Bartolini et al (2016) tent. Simultaneously, budget expenditures make the development of regions even more uneven in terms of socio-economic indicators.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The number of causes of regional divergence identified by these methods is quite large. Thus, Bartolini et al (2016) tent. Simultaneously, budget expenditures make the development of regions even more uneven in terms of socio-economic indicators.…”
Section: Literature Reviewmentioning
confidence: 95%
“…While economic disparities among OECD countries have been diminishing, the long-term trend of increasing inequality among regions has continued. Economic disparities between regions are now higher than they were a decade or two ago (Bartolini et al, 2016). This trend is reflected in significant regional disparities in labour productivity across the OECD ( Figure 1.1).…”
Section: The Challenge Of Widening Economic Disparities Across Regionsmentioning
confidence: 98%
“…Savy, Pauliat, and Senimon (2016) examined the decentralization processes in Europe, concluding that they are non-linear and different, depending on the size of the region, the traditions of self-government, the role of the central government, and other political, social, economic, and cultural characteristics. Bartolini, Stossberg, and Blöchliger (2016) have argued that fiscal policy decentralization reforms must be two-sided: the growth of local budget revenues should be matched by adjustment of intergovernmental transfers and fiscal equalization. Bartolini, Stossberg, and Blöchliger (2016) examined the relationship between regional inequality in the countries and the state of fiscal decentralization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bartolini, Stossberg, and Blöchliger (2016) have argued that fiscal policy decentralization reforms must be two-sided: the growth of local budget revenues should be matched by adjustment of intergovernmental transfers and fiscal equalization. Bartolini, Stossberg, and Blöchliger (2016) examined the relationship between regional inequality in the countries and the state of fiscal decentralization. The results of an analysis of 30 OECD countries in 1995-2011 have shown that in those countries where local government budgets are mainly financed by local taxes, local resources are used more effectively, and fiscal policy is stepping up territorial development.…”
Section: Literature Reviewmentioning
confidence: 99%